The Diagnosis of Asthma - Nick R Anthonisen (Canadian Respiratory Journal)
In this issue of the Canadian Respiratory Journal, LindenSmith et al (pages 111 to 116) present data that strongly suggest that patients who do not have asthma frequently acquire this diagnosis. They recruited 90 adults who thought that they had asthma and, in fact, had symptoms of asthma, and found that over 40% of them did not have objective evidence of the disease; of these, 43% were taking inhaled corticosteroids. Objective evidence was defined as demonstrable reversible airways obstruction, meaning spirometric response to inhaled bronchodilators, diurnal peak flow variability and/or methacholine responsiveness. Of these, methacholine response was by far the most important; in fact, a confirmed diagnosis amounted to symptoms plus methacholine sensitivity. The authors discussed possible reasons for lack of methacholine responsiveness in people who really have asthma, but were unconvinced that these were important confounders in their study and cited other studies that have also found that asthma is overdiagnosed.